New Class of Conjugate Gradient Methods for Removing Impulse Noise Images - Abbo, hameed; Hassan , Basim (Iraqi Journal of Science, 2023)
The conjugate coefficient optimal is the very establishment of a variety of  conjugate gradient methods. This paper proposes a new class coefficient of conjugate gradient (CG) methods for impulse noise removal, which is based on the quadratic model. Our proposed method ensures descent independent of the accuracy of the line search and it is globally convergent under some conditions, Numerical experiments are also presented for the impulse noise removal in images.